Expression of VEGFA-mRNA in classical and MSX2-mRNA in non-classical monocytes in patients with spondyloarthritis is associated with peripheral arthritis - Stec, Małgorzata (Sci Rep, 2021)
Spondyloarthritis (SpA) is characterized by chronic inflammation and structural damage involving spine and peripheral joints. Monocytes, as part of innate immune system, following migration into affected tissue, may play a role in the pathogenesis of SpA. Here, potential associations between osteogenesis-linked gene expression profile in particular monocyte subpopulations and clinical signs of SpA were investigated. The 20 patients with axial and 16 with peripheral SpA were enrolled in the study. Monocyte subpopulations (classical—CD14(++)CD16(−), intermediate—CD14(++)CD16(+) and non-classical—CD14(+)CD16(++)) were isolated from blood using flow cytometry and gene expression analysis was performed using real-time PCR method and TaqMan Array, Human Osteogenesis, Fast 96-well plates. Next, the characteristic clinical features shared by axial and peripheral SpA were analyzed in the context of the expression of selected genes in the three subpopulations of monocytes. We demonstrated that expression of VEGFA in classical and MSX2 in non-classical monocytes were associated with the number of swollen and painful peripheral joints of SpA patients. We conclude that monocytes may contribute to the development of peripheral arthritis in SpA patients. This might be possible through subpopulation specific effects, linking number of inflamed joints with expression of VEGFA in classical monocytes and MSX2 in non-classical monocytes.